(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2018)
Coastal ecosystems are ecologically, socially, and monetarily significant, and consequently are feeling the squeeze from various human exercises. The impression of coastal zone management is a nearly new one, promising under four decades back from the necessity to handle a scope of interrelated issues associated with population development and improvement along our country’s coasts. Because of present population development and advancement coastal regions worldwide are under rising weight. Also increased misuse of non-sustainable resources is spoiling the reasons and estimations of coastal zones in numerous pieces of the world. So the sustainable coastal zone management is essential. The methodologies of the sustainable coastal zone management are portrayed in the present endeavor.